2015
DOI: 10.3389/fnhum.2015.00169
|View full text |Cite
|
Sign up to set email alerts
|

Bimanual Elbow Robotic Orthoses: Preliminary Investigations on an Impairment Force-Feedback Rehabilitation Method

Abstract: Modern rehabilitation practices have begun integrating robots, recognizing their significant role in recovery. New and alternative stroke rehabilitation treatments are essential to enhance efficacy and mitigate associated health costs. Today’s robotic interventions can play a significant role in advancing rehabilitation. In addition, robots have an inherent ability to perform tasks accurately and reliably and are typically well suited to measure and quantify performance. Most rehabilitation strategies predomin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 62 publications
0
9
0
Order By: Relevance
“…The different time length between two positionings yielded different perceptions in the participant, which is called a Tau effect [74]. Herrnstadt et al [18] have suggested that the need to memorize the location of an arm is eliminated, but the Tau effect might have been triggered, influencing the participant’s judgement. Additionally, passive arm positioning was shown to result in larger errors compared to active arm positioning [75].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The different time length between two positionings yielded different perceptions in the participant, which is called a Tau effect [74]. Herrnstadt et al [18] have suggested that the need to memorize the location of an arm is eliminated, but the Tau effect might have been triggered, influencing the participant’s judgement. Additionally, passive arm positioning was shown to result in larger errors compared to active arm positioning [75].…”
Section: Discussionmentioning
confidence: 99%
“…They concluded that pure bilateral or active and/or passive movement training protocols do not contribute to significant motor recovery. The applications of bimanual training with robots [18,19,20] and rhythmic auditory cueing [21] were investigated in the rehabilitation of stroke survivors. The possibility of the concept of bimanual training and companied devices in extending contemporary therapies is accepted.…”
Section: Introductionmentioning
confidence: 99%
“…A master-slave system is used in robotic surgery 12) and in an upper limb rehabilitation robot. 13) Such a master-slave robot can achieve an adequate trajectory for an individual patient without any previous data or calculation. For hemiplegics, a master-slave robotic rehabilitation system for the lower limb that uses a feedback system from the non-affected limb has not before been attempted.…”
Section: Discussionmentioning
confidence: 99%
“…These drawbacks motivated researchers to find solutions to minimize the human labor and thus decrease rehabilitation cost (Freeman et al, 2009 ; Poli et al, 2013 ). Most robotic devices are capable of passively delivering a high number of training repetitions to the stroke-affected limb (Freeman et al, 2009 ; Loureiro et al, 2011 ; Ren et al, 2013 ; Herrnstadt et al, 2015 ; Proietti and Crocher, 2016 ). However, clinical evidence suggests that users' engagement plays an important role to enable and augment motor recovery (Hogan et al, 2006 ; Krebs et al, 2009 ; Lo and Xie, 2012 ).…”
Section: Introductionmentioning
confidence: 99%